From Chalkboards to Chatrooms: Systematic Review of ICT Integration in Nepalese ELT Classrooms - Dhakal, Narayan Prasad (Devkota Journal of Interdisciplinary Studies, 2025)
The incorporation of digital tools in English language instruction has become an essential aspect of contemporary pedagogy, providing diverse avenues to enrich teaching and learning processes. This study investigates the integration of educational technology within the context of English Language Teaching (ELT) in Nepal by conducting a systematic analysis of 40 peer-reviewed publications from the past ten years. The review identifies widely adopted digital resources, including virtual learning environments, mobile-assisted language learning apps, and multimedia tools, assessing both their pedagogical benefits and the limitations they present. A key focus is placed on educators’ digital skillsets, which were found to vary considerably, falling into categories of advanced, intermediate, or foundational competence. The majority of teachers demonstrated a pressing need for further training to fully utilize digital innovations in the classroom. Contributing factors influencing the adoption of such technologies – such as institutional backing, availability of resources, and educators’ perceptions – were also examined. Nonetheless, the review identifies critical gaps in existing literature, notably the lack of a unified framework for evaluating digital proficiency, limited longitudinal evidence on the impact of technology on learning achievements, and insufficient research addressing the specific challenges encountered by instructors in low-resource settings like rural Nepal. These insights underline the necessity for targeted capacity-building initiatives, alongside the development of resilient technological infrastructure to close the competency divide. Although this study contributes to the growing body of knowledge on digital transformation in ELT, its findings are tempered by limitations including geographic concentration and the exclusive reliance on secondary data. Future inquiry is recommended to broaden the geographical lens, investigate new-generation technologies, and deepen understanding of sustainable technology integration in English education within the diverse socio-educational landscapes of Nepal.